Straightforward Stepwise Excited State Dual Proton Transfer Mechanism for 9-10-HBQ System (Communications in Computational Chemistry, 2017)
A new molecule 9,10-dihydroxybenzo[h] quinoline (i.e. 9-10-HBQ) is focusedin the present work about its excited state proton transfer (ESPT) mechanism. Thoughcomparing potential energy barriers, it is found that the ultrafast ESPT process couldoccur in the $S_1$ state without potential energy barrier along with hydrogen bond $O_3$-$H_4···N_5$ forming 9-10-HBQ-PT1 structure, subsequently, the second proton transfersvia another intramolecular hydrogen bonded wire $O_1$-$H_2···N_3$ with a low potentialenergy barrier (about 7.69 kcal/mol) in the $S_1$ state forming 9-10-HBQ-PT2 configuration.After completing excited state dynamical process, the $S_1$-state could turn back to $S_0$ statewith occurring reversed ground state proton transfer forming initial 9-10-HBQstructure.